Utilization of the Educaplay Website Application as a Learning Medium to Enhance Elementary School Students’ Creative Thinking - Adinda Nihlah Alkhusufiah; Ratnasari Dyah Utami (Journal of Educational Sciences, 2026)
Creativity is one of the essential abilities that needs to be developed from the elementary school level. In line with technological advancements, interactive learning media such as Educaplay can serve as a means to enhance students’ creativity. This study aimed to describe the utilization of the Educaplay website application in IPAS learning and its influence on students’ creative thinking at SD Muhammadiyah Program Unggulan Colomadu. The research employed a descriptive qualitative approach using observation, interview, and documentation techniques. Data validity was ensured through source, technique, and time triangulation. The results indicate that Educaplay is able to improve students’ creative thinking in three main indicators: fluency, flexibility, and curiosity. Students became more active, enthusiastic, and capable of generating diverse ideas through interactive game-based activities. Teachers experienced greater ease in delivering materials and conducting evaluations due to the visual and audio features as well as automatic feedback. The main obstacles encountered were related to internet connectivity and adaptation to the use of the media; however, these were addressed through network checks, the use of personal hotspots, and the provision of alternative learning activities. Overall, Educaplay is effective as a learning medium for enhancing elementary school students’ creative thinking.